Caracterização de requeijão cremoso potencialmente prebiótico pela adição de inulina e proteína de soja - Gomes, Raquel Guttierres [UNESP]; Penna, Ana Lúcia Barreto [UNESP] (My University, 2010)
Requeijão is a typical Brazilian cheese and exhibits a significant consumption in the domestic market and presents high potential for functional foods. In this study the physicochemical characterization of requeijão cheese added of dairy cream, hydrogenated vegetal fat, soy protein isolate and inulin was carried out. For the requeijão cheese making it was used: Lactic mass, sodium chloride, melting salt, starch, whey protein concentrate, xanthan gum, nisin and water. Dairy cream (2.0; 4.0 and 6.0%), hydrogenated vegetable fat (6.0; 8.0 and 10.0%), soy protein isolate - SPI (0.5; 1.0 and 1.5%) and inulin (3.8; 5.05 and 6.3%) were added, according to the trial. The formulated products presented 6.26 to 6.38 of pH value, 0.24 to 0.39% of acidity, 7.29 to 10.04% of protein, 1.62 to 1.77% of ashes, 12.5 to 21.3% of fat, 39.8 to 66.1% of fat dry matter and 28.63 to 35.56% of total solids. The developed requeijão cheeses added of soy protein isolate and inulin are feasible alternatives for healthy foods and potentially prebiotics.
Characterization of requeijão cheese potentially prebiotic by the addition of inulin and soy protein
Keywords: Funcional foods; Inlulin; Processed cheese; Soy protein isolate; Glycine max